Methods to construct a step-by-step beginner’s guide to decision analytic cost-effectiveness modeling - Rautenberg T; Hulme C; Edlin R (Dove Medical Press, 2016)
Tamlyn Rautenberg,1 Claire Hulme,2 Richard Edlin,3 1Health Economics and HIV/AIDS Research Division (HEARD), University of Kwazulu Natal, KwaZulu Natal, South Africa; 2Leeds Institute of Health Sciences (LIHS), Academic Unit of Health Economics (AUHE), University of Leeds, West Yorkshire, United Kingdom; 3Faculty of Medical and Health Sciences, University of Auckland, Auckland, New Zealand Background: Although guidance on good research practice in health economic modeling is widely available, there is still a need for a simpler instructive resource which could guide a beginner modeler alongside modeling for the first time. Aim: To develop a beginner’s guide to be used as a handheld guide contemporaneous to the model development process. Methods: A systematic review of best practice guidelines was used to construct a framework of steps undertaken during the model development process. Focused methods review supplemented this framework. Consensus was obtained among a group of model developers to review and finalize the content of the preliminary beginner’s guide. The final beginner’s guide was used to develop cost-effectiveness models. Results: Thirty-two best practice guidelines were data extracted, synthesized, and critically evaluated to identify steps for model development, which formed a framework for the beginner’s guide. Within five phases of model development, eight broad submethods were identified and 19 methodological reviews were conducted to develop the content of the draft beginner’s guide. Two rounds of consensus agreement were undertaken to reach agreement on the final beginner’s guide. To assess fitness for purpose (ease of use and completeness), models were developed independently and by the researcher using the beginner’s guide. Conclusion: A combination of systematic review, methods reviews, consensus agreement, and validation was used to construct a step-by-step beginner’s guide for developing decision analytical cost-effectiveness models. The final beginner’s guide is a step-by-step resource to accompany the model development process from understanding the problem to be modeled, model conceptualization, model implementation, and model checking through to reporting of the model results. Keywords: step-by-step guide, modeling, cost-effectiveness analysis, decision analysis, economic evaluation